Synthesis and structure elucidation of some 4-substituted benzylidene amino-5-[3(5)-methyl-5(3)-phenyl-1H-1-pyrazolyl]-2,4-dihydro-3H-1,2,4-triazole -3-thione derivatives with their antimicrobial activities - (:unkn) unknown (My University, 1997)
A new series of 4-substituted benzylideneamino-5[3(5)-methyl-5(3)-phenyl-1H-1-pyrazolyl]-2,4-dihydro-3H-1,2, 4-triazole-3-thione was synthesized by reaction of I with suitable aldehyde and tested for their antimicrobial activities against six microorganisms. Most of the compounds showed antibacterial activity against Gram positive bacteria.